Total Plate Count of Germs on Pear Surface Swabs During Washing with Fruit Washing Soap - Defitri Afira; Suparno Putera Makkadafi; Nurul Anggraeni (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The surface of the fruit is the first contamination of microorganisms on fruit with varying types and amounts. As many as 20% of cases of food poisoning caused by Salmonella typhi were recorded as a result of the consumption of fresh ready-to-eat products such as fruits. Washing the fruits that will be consumed is a good step, so a fruit washing soap product is used that can clean the fruits from these bacteria. Nonionic surfactants are cleaning agents found in fruit washing soaps that can remove bacteria on surfaces. The purpose of this study was to determine the difference in the total plate number of germs on the surface of pears when washing with fruit washing soap. The research method used in this research is descriptive method. The population is 50 soaps taken from 5 shops in the Harapan Baru market in Samarinda with different soap brands. The sample taken is 10% of the total population, namely 5 soaps. The sampling technique used purposive sampling. The study was carried out in July 2022. The method of examination used the examination of the TPC (Total Plate Count) with the pour plate method using PCA (Plate Count Agar) media. The data analysis used is univariate analysis which aims to explain the characteristics of each research variable by looking at the frequency distribution. The results showed that the number of bacteria before washing with fruit washing soap ranged from 4.4 x 100 CFU/cm2 to 1.4 x 101 CFU/cm2. Meanwhile, the number of bacteria after washing with fruit washing soap ranged from 0.4 x 100 CFU/cm2 to 3.4 x 100 CFU/cm2. The conclusion of this study is that there are differences in the number of total bacterial plate count on the surface of pears when washing with fruit washing soap.